The Immigrant Cookbook: Recipes That Make America Great - Leyla Moushabeck (Interlink Pub Group, 2017)
More than 42 million people living in the United States came here from other countries. Since its beginnings, America has been a haven for people seeking refuge from political or economic troubles, or simply those in search of adventure and prosperity in a land where opportunity is promised to all. These Ã©migrÃ©s, from every corner of the world, helped make America great long before the 2016 election.